2021
DOI: 10.1101/2021.02.26.433024
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

THz irradiation inhibits cell division by affecting actin dynamics

Abstract: Biological phenomena induced by terahertz (THz) irradiation are described in recent reports, but underlying mechanisms, structural and dynamical change of specific molecules are still unclear. In this paper, we performed time-lapse morphological analysis of human cells and found that THz irradiation halts cell division at cytokinesis. At the end of cytokinesis, the contractile ring, which consists of filamentous actin (F-actin), needs to disappear; however, it remained for 1 hour under THz irradiation. Inducti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…There exist conflicting reports with some authors suggesting that THz collapses actin filaments [28] while others claim an enhancement of actin fibrils lengthening dynamics [29]. It has also been observed that cellular division is inhibited via actin-mediated interferences [30].…”
Section: Interaction With Animal Tissue and Cellsmentioning
confidence: 99%
“…There exist conflicting reports with some authors suggesting that THz collapses actin filaments [28] while others claim an enhancement of actin fibrils lengthening dynamics [29]. It has also been observed that cellular division is inhibited via actin-mediated interferences [30].…”
Section: Interaction With Animal Tissue and Cellsmentioning
confidence: 99%